The Importance of New Ways of Working to Influence Workforce Agility in The Manufacturing Sector for Managing Destructive Situation - Fransiska Cicilia Pembayun Noviansista Cornelis; Hary Febriansyah (Department of Management, Faculty of Economics and Business, Brawijaya University, 2023)
After the COVID-19 pandemic, the manufacturing industry could quickly regain its performance. The question remains whether new ways of working (NWW) contribute to this adaptable behaviour of manufacturing employees. Implementing NWW techniques in manufacturing varies since the production process includes primary and secondary activities. Moreover, Psychological Empowerment plays a role in Workforce Agility in terms of employee sustainability as a human who requires intrinsic motivation to cope with any environment. This study surveyed 233 manufacturing employees in Indonesia and used SEM-PLS to determine the importance of applying NWW for manufacturing to attain its agility, particularly in the human factor. The results indicate that NWW has a positive effect on Workforce Agility. The authors conclude with discussions and the implications of implementing NWW in the industrial sector based on the supported proposed model.